Pengaruh Kecerdasan Emosional dan Kecerdasan Spiritual terhadap Adaptasi Sosial Siswa - Muhammad Zaki Ridho Djakfar; Mohamad Agung Rokhimawan; Vikri Aflaha Qomari (Universitas Negeri Padang, 2025)
This study aims to analyze the influence of emotional intelligence and spiritual intelligence on the social adaptation of master's degree students in the Islamic Religious Education program. The main issue addressed is the lack of students’ ability to adapt socially in the university environment. To address this, a quantitative approach with a survey method was employed, using multiple linear regression analysis. The sample consisted of 48 students selected through stratified random sampling. Data were collected using a closed-ended questionnaire on a Likert scale. Validity and reliability tests confirmed that the instrument was both valid and reliable. Data analysis included normality, linearity, t-test, F-test, and determination coefficient (R²). The results showed that both emotional and spiritual intelligence significantly influence social adaptation, both partially and simultaneously. The R² value of 0.663 indicates that the independent variables explain 66.3% of the variation in social adaptation. The study concludes that strengthening emotional and spiritual competencies is a key strategy to improve students' social adaptation. It recommends the integration of emotional and spiritual intelligence development into student development programs in Islamic higher education institutions.